Comparative Literature Study of Little Women Movie in American Version and Korean Version - Fatimah Zanita Zanuba; Ana Widiyanti (Metaphor, 2024)
This research aims to analyze : (1) the temperament of the characters in the American and Korean versions of the film Little Women, (2) the comparison of human temperaments in the American and Korean versions of the film Little Women. The study uses a descriptive qualitative method to analyze the objective of the research, which is Little Women (2019) American movie directed by Greta Gerwig, and Little Women (2022) Korean drama directed by Kim Hee Won. The researcher analyzes the data by using a Comparative Literature Study with the Human Temperament theory by Immanuel Kant. The result of the study : (1) the characters’ temperament of soul presented in the Little Women (2019) movie and Little Women (2022) Korean drama is Choleric Temperament in characters Jo March and Oh In-Kyung, Phlegmatic Temperament in the character Meg March and Oh In-Hye, Melancholic Temperament in character Beth March and Oh In-Joo, and Sanguinis Temperament in character Amy March; (2) the comparison of the characters’ temperament of the Korean drama Little Women (2022) is inversely proportional to the characters’ temperament of the film Little Women (2019). This is mainly due to the very different backgrounds in both. The film Little Women (2019) is set in the 1980s, whereas the Korean drama Little Women (2022) is set in the present age. With such different socio-cultural conditions, the depiction of the human temperament in the scenes is very different.